Routine or selective carotid artery shunting for carotid endarterectomy (and different methods of monitoring in selective shunting). - Bond, R; Rerkasem, K; Counsell, C; Salinas, R; Naylor, R; Warlow, C; Rothwell, P (2002)
BACKGROUND: Temporary interruption of cerebral blood flow during carotid endarterectomy can be avoided by using a shunt across the clamped section of the carotid artery. This may improve outcome. OBJECTIVES: The objective of this review was to assess the effect of routine versus selective, or never, shunting during carotid endarterectomy, and to assess the best method for selecting patients for shunting. SEARCH STRATEGY: For the original review the authors searched the Cochrane Stroke Group trials register, Medline (1966 to 1994), Embase (1980 to 1995) and Index to Scientific and Technical Proceedings (1980 to 1994). They also hand searched Annals of Surgery (1981 to 1995), British Journal of Surgery (1985 to 1995), European Journal of Vascular Surgery (1988 to 1995) and World Journal of Surgery (1978 to 1995). For the updated review, for the dates January 1994 - December 2000 we: 1. Repeated all these searches performed for the original review and developed more comprehensive search strategies for Medline and Embase. The Cochrane Stroke Group Trials Register was last searched in May 2001. 2. Hand searched the Journal of Vascular Surgery, Stroke, Annals of Vascular Surgery, American Journal of Surgery and Cardiovascular Surgery. 3. Hand searched the abstracts from the International Stroke Conference, AGM of the Vascular Surgical Society (UK), AGM of the Association of Surgeons of Great Britain and Ireland and the Annual Meeting of the Society for Vascular Surgery (USA). 4. Searched reference lists from all relevant trials All the authors of studies included in the initial review, and other authors known to have published relevant work, were contacted requesting information about further published or unpublished data. SELECTION CRITERIA: Randomised and quasi-randomised trials of routine shunting compared with no shunting or selective shunting, and trials that compared different shunting policies in patients undergoing carotid endarterectomy. DATA COLLECTION AND ANALYSIS: For the original review two reviewers independently performed the searches and applied the inclusion criteria. The data were extracted by one reviewer and double-checked. Trial quality was assessed. During the update, two reviewers independently performed the searches and applied the inclusion criteria. No new relevant randomised controlled trials were found. MAIN RESULTS: Despite recommendation from the original review that further studies were required, no new trials of adequate quality and fitting the inclusion criteria were found. The initial review included three trials. Two trials involving 590 patients compared routine shunting with no shunting. The other trial involving 131 patients compared shunting with a combination of electroencephalographic and carotid pressure measurement, with shunting by carotid pressure measurement alone. Allocation was adequately concealed in one trial, and one trial was quasi-randomised. Analysis was by intention-to-treat where possible. For routine versus no shunting, there was no significant difference in the rate of all stroke, ipsilateral stroke or death up to 30 days after surgery, although data were limited. There was no significant difference between the risk of ipsilateral stroke in patients selected for shunting with the combination of electroencephalographic and carotid pressure assessment compared to pressure assessment alone, although again the data were limited. REVIEWER'S CONCLUSIONS: When first published in 1995, this review concluded that the data available were too limited to either support or refute the use of routine or selective shunting in carotid endarterectomy. It was suggested that large scale randomised trials using no shunting as the control group were required. No one method of monitoring in selective shunting has been shown to produce better outcomes. No further prospective randomised or quasi-randomised trials have been performed since then and the conclusions therefore remain unchanged.